An effective electrolyte design to improve the high-voltage performance of high-capacity NCM811 / SiOx-Gr batteries. (20th July 2020) - Kong, Xiangbang; Liu, Junjie; Zhang, Yige; Zeng, Jing; Zhao, Jinbao
Abstract: Increasing the charge voltage of a battery can greatly augment its specific capacity, but the increase of the voltage often brings some negative effects. Among them, the decomposition of the electrolyte at high voltage is a very serious problem. In this work, theoretical calculations are used to combine the advantages of each solvent, so that the designed electrolyte can effectively strengthen the high-voltage property of high-capacity NCM811/SiOx -Gr system batteries. The additive sulfolane is adopted to be oxidized in advance and build a protective film around the LiNi0·8 Co0·1 Mn0·1 O2 positive electrode, and fluoroethylene carbonate is employed to be priorly reduced and form a film on the face of silicon oxide-graphite negative electrode. Compared with the traditional electrolyte, the cycling retention rate of the full battery is increased from 58.44% to 77.51% after cycling for 200 times under the voltage of 4.5 V with the high-performance electrolyte. From the results of a series of tests, it can be found that the high-voltage electrolyte can effectually maintain the structural of the cathode and anode materials at high voltages and improve the electrochemical performance. In addition, the electrolyte also has high conductivity and wettability with separator, which brings it a good application prospect. Highlights: Greatly improve high-voltage performance of high-capacity NCM811/SiOx-Gr batteries. Significantly improve the stability of silicon-based anode materials under high voltages. Enhance the resistance of high nickel cathode materials under high voltage. Have better wettability with the separator, have the potential for large-scale applications.